Economic Policy Uncertainty and Government Bond Prices - Faniband, Muhammadriyaj; Jadhav, Pravin (Indian Journal of Finance, 2023)
Purpose : This paper investigated the impact of economic policy uncertainty (EPU) in the US, UK, Japan, Italy, India, Germany, France, China, Canada, and Brazil on Indian government bond prices using a new dataset of the Clearing Corporation of India Limited Broad Total Return Index (BTRI) and Liquid Total Return Index (LTRI). Methodology : We used the quantile regression approach and monthly dataset from January 2004 – December 2020 for the analysis. Findings : We found that the top 20 government bond prices decreased due to EPU in India, Japan, the US, and the UK. In contrast, the EPU of Canada, China, and the UK had a statistically significant positive impact on BTRI. Further, a negative relationship was found between the top five government bond prices and the EPU of three economies: India, Japan, and the US. Practical Implications : The analysis will help identify potential risks and vulnerabilities in government bonds. It assists regulators and policymakers in implementing effective risk management measures to safeguard financial stability. The findings will also be useful for investors and market participants to make informed investment decisions. Originality : From a data standpoint, this is the first study that used CCIL’s BTRI and LTRI data for the first time to canvass the impact of EPU on Indian government bonds as far as we know. Further, we took into account the unique characteristics of the EPU of the top 10 economies and directly compared the reaction of these economies’ EPU to the government bond price fluctuations.